2020
DOI: 10.7717/peerj-cs.267
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of data mining methodologies: a systematic literature review

Abstract: The use of end-to-end data mining methodologies such as CRISP-DM, KDD process, and SEMMA has grown substantially over the past decade. However, little is known as to how these methodologies are used in practice. In particular, the question of whether data mining methodologies are used ‘as-is’ or adapted for specific purposes, has not been thoroughly investigated. This article addresses this gap via a systematic literature review focused on the context in which data mining methodologies are used and the adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 107 publications
(144 reference statements)
1
18
0
8
Order By: Relevance
“…For this, numerous process models exist. MARISCAL et al and PLOTNIKOVA et al provide an overview about existing process models and show that almost all identified approaches are based on two original models: the Cross Industry Standard Process for Data Mining (CRISP-DM) and the Knowledge Discovery in Databases model (KDD) [33,34]. Therefore, these two models are subsequently described in more detail.…”
Section: Model Constructionmentioning
confidence: 99%
“…For this, numerous process models exist. MARISCAL et al and PLOTNIKOVA et al provide an overview about existing process models and show that almost all identified approaches are based on two original models: the Cross Industry Standard Process for Data Mining (CRISP-DM) and the Knowledge Discovery in Databases model (KDD) [33,34]. Therefore, these two models are subsequently described in more detail.…”
Section: Model Constructionmentioning
confidence: 99%
“…Penelitian ini menggunakan tahapan Cross-Industry Standard Process Model for Data Mining (CRISP-DM) dalam penerapan algoritme k-NN dan Naïve Bayes dengan Backward Elimination pada klasifikasi kepuasan pelanggan. CRISP-DM bertujuan untuk memberikan pedoman kepada praktisi untuk melakukan penambangan data pada set data besar (Plotnikova et al, 2020). Adapun tahapannya dapat dilihat pada Gambar 1.…”
Section: Metodologi Penelitianunclassified
“…Biasanya, beberapa teknik digunakan untuk menangani masalah data mining yang serupa. Pada penelitian ini teknik klasifikasi dipilih untuk membandingkan penerapan algoritme k-NN dengan dan tanpa Backward Elimination, serta algoritme Naïve Bayes dengan dan tanpa Backward Elimination [17].…”
Section: Modellingunclassified
“…It is one part of computer science that is bound up with disciplines such as statistics, probability, artificial intelligence, and machine learning, which has become a good research field that has gained a lot of attention due to its approach to data processing and information discovery [1], [2], [16]. Besides, it is defined as a set of rules, procedures, and algorithms to produce valuable insights, derive patterns, and draw connections from huge datasets [16]. It also incorporates advanced data retrieval, processing and simulation using several methods and techniques.…”
Section: B Data Miningmentioning
confidence: 99%
“…Several major data mining techniques have been developed and applied in pandemic outbreaks such as classification, clustering, and association rules. Classification is a method that allocates objects in a series to target groups whereby the same set of features is put into a class by this approach [16]. Naïve Bayes, Decision Tree, Artificial Neural Network, Support Vector Machine, Associative Classification and K-Nearest Neighbours are some of the methods of classification [2].…”
Section: B Data Miningmentioning
confidence: 99%